PERBEDAAN TEKNIK MORDANTING TERHADAP HASIL PENCELUPAN ZAT WARNA ALAM EKSTRAK DAUN KELADI HIAS (Philodendron) DENGAN MORDAN AIR TAPAI PADA BAHAN SUTERA - AMELIA, ELSA; Adriani, Adriani; Idrus, Yenni (Journal of Home Economics and Tourism, 2015)
This study is a True-experiment to reveal differences mordanting techniques to result mordant dyeing silk material with water Tapai. This study aimed to describe: 1) the name of the color (hue) 2) Dark bright color (Value) 3) Flatness Color and differences resulting from dyeing silk using ornamental taro leaf extract (Philodendron) with water mordant Tapai using the technique of pre-mordanting , meta-mordanting and post-mordanting.The data used is primary data obtained from the results of experiments using the silk material of ornamental taro leaf extract (Philodendron) with water mordant Tapai. The object is a silk cloth dipped with ornamental taro leaf extract (Philodendron) using pre-mordanting techniques, meta-mordanting and post-mordanting. The research data was obtained by spreading the research instrument which is based rating scale, which is distributed to the panelists. Research procedures performed with several stages, namely: 1) the preparation phase 2) Phase 3 implementation) stage of completion, and 4) assessment stage of data analysis techniques performed with SPSS (Statistical Product And Service Solution) version 16.0 using the formula F test (Fisher Test).From the experimental results it can be seen that the dyeing silk using ornamental taro leaf extract (Philodendron) with water mordant Tapai using pre-mordanting techniques, meta-mordanting and post-mordanting produce the same colors that Indian Red (red indian). The results of the data analysis bright dark color (value) indicates Fhitung> Ftable = 2935> 3.22 means that there is no significant difference on the bright dark color (value). In flatness color indicates Fhitung <Ftabel = 199 <3.22. This means that there is no difference flatness of color due to differences in technique mordant in dyeing silk using ornamental taro